The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1152/ajpregu.00688.2004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in PKB/Akt and calcineurin signaling during recovery in atrophied soleus muscle induced by unloading

Abstract: . Changes in PKB/Akt and calcineurin signaling during recovery in atrophied soleus muscle induced by unloading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
59
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 34 publications
14
59
1
Order By: Relevance
“…Although Akt phosphorylation appeared to be attenuated after HS, this effect did not reach statistical significance in either muscle. This may be attributed to the low baseline levels of Akt phosphorylation in both muscles, because previous studies showed that skeletal muscle unloading or inactivity is accompanied by decreased Akt phosphorylation (29,53). Subsequently, consequent to decreased Akt activity, reduced mRNA translation (2, 10) and increased protein degradation resulting from decreased suppression of atrogin expression (46) likely contributed to the loss of muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…Although Akt phosphorylation appeared to be attenuated after HS, this effect did not reach statistical significance in either muscle. This may be attributed to the low baseline levels of Akt phosphorylation in both muscles, because previous studies showed that skeletal muscle unloading or inactivity is accompanied by decreased Akt phosphorylation (29,53). Subsequently, consequent to decreased Akt activity, reduced mRNA translation (2, 10) and increased protein degradation resulting from decreased suppression of atrogin expression (46) likely contributed to the loss of muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the classic anabolic and catabolic pathways are affected in response to denervation and inactivity. Myostatin expression is increased (94) and activation of Akt is decreased (104) in inactive skeletal muscle. Recently, some novel mechanisms have been implicated in denervation and unloading-induced atrophy.…”
Section: Tgf-␤mentioning
confidence: 98%
“…In addition, most of the genes downregulated and several genes upregulated during unloading return to basal levels within a few hours of recovery (78). These effects result in relatively rapid recovery of the fiber cross-sectional area (135,138) and muscle mass (15,(136)(137)(138)(139)(140)(141).…”
Section: 1) Myofiber Damage and Recovery Of Muscle Massmentioning
confidence: 99%
“…In addition, others have demonstrated that the downstream pathway of Akt, including ribosomal protein S6, is activated early in recovery from disuse muscle (soleus) atrophy, suggesting that the recovery of atrophied muscles is facilitated by increased mRNA translation during the early stages of resumption of loading (140). Moreover, another study concluded that a 2-wk recovery period from nonweight bearing significantly increases the activation levels of S6K and ribosomal protein S6 in medial gastrocnemius muscles of sham-operated (ovariectomy) rats, but does not influence appreciably the levels of phosphorylated Akt or mTOR in the same animals (141).…”
Section: 2) Reactivation Of the Protein Synthetic Machinerymentioning
confidence: 99%